Analisis Keberlanjutan Usaha Budidaya Pembibitan Ikan Lele Di Desa Hang Tuah, Kecamatan Perhentian Raja, Kabupaten Kampar, Riau - Putri, Vivian; Ekwarso, Hendro; Taryono, Taryono (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study examines the sustainability of catfish (Clarias sp.) hatchery farming in Hang Tuah Village, Perhentian Raja Subdistrict, Kampar Regency, Riau, using a quantitative descriptive approach. The research population consisted of 220 catfish farmers, with a sample of 69 respondents selected through purposive sampling. The results indicate an average production of 66,188 fingerlings per cycle, generating an average revenue of IDR 7,942,609 and production costs of IDR 4,664,077, resulting in a net income of IDR 3,258,532. These findings demonstrate that catfish hatchery farming is profitable and has strong development potential. Labor elasticity was estimated at 4.15, meaning a 1% increase in labor input could raise output by approximately 4.15%, highlighting the labor-intensive nature of the business. However, labor productivity slightly declined from 91,668 to 83,668 fingerlings per worker, as labor growth outpaced production growth. Overall, the sustainability index reached 72.91, classified as moderately sustainable. Strengthening marketing strategies, enhancing community training, and adopting climate adaptation measures are essential to ensure long-term sustainability and optimize economic benefits for local communities.